2022
DOI: 10.18585/inabj.v14i3.2032
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic Acid Induces Intrinsic Apoptotic Pathway in MG-63 Osteosarcoma Cells Through Bid Truncation and Cytochrome c Release

Abstract: BACKGROUND: Caffeic acid has been reported to induce apoptosis in MG-63 osteosarcoma cells via caspases activation. However, apoptotic pathway that is involved in the caffeic acid-induced apoptosis is still unclear. Present study aimed to investigate the role of cytochrome c (Cyt c) release and BH3-interacting death (Bid) activation in caffeic acid-induced apoptosis in MG-63 osteosarcoma cells.METHODS: MG-63 cells were cultured, pretreated with/without Z-VAD FMK and treated with/without 10 μg/mL caffeic acid. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…This result suggested that caffeic acid might induces MG-63 cells into apoptosis. (3,11) Only few studies regarding this was conducted on MG-63 cells-induced mice, however the result of this current study is in line with a study on B7-P815 cellsinduced mice which also showed that ingested caffeic acid significantly hinders tumour growth in the terms of size. (20) Previous study on multiple myeloma cells, ARH-77, also shows that a derivative of caffeic acid, namely the caffeic acid phenethyl ester, is able to inhibit the tumour growth and induces cell death in a dose-and time-dependent manner.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This result suggested that caffeic acid might induces MG-63 cells into apoptosis. (3,11) Only few studies regarding this was conducted on MG-63 cells-induced mice, however the result of this current study is in line with a study on B7-P815 cellsinduced mice which also showed that ingested caffeic acid significantly hinders tumour growth in the terms of size. (20) Previous study on multiple myeloma cells, ARH-77, also shows that a derivative of caffeic acid, namely the caffeic acid phenethyl ester, is able to inhibit the tumour growth and induces cell death in a dose-and time-dependent manner.…”
Section: Discussionsupporting
confidence: 89%
“…This result suggested that caffeic acid pre-treatment promote the cell death of MG-63 population. (3) Bigger mass nodule in the subcutaneous area was also observed in the untreated MG-63 cells-induced mice compared to the one that received intra-tumour injection of caffeic acid. This proved that the effectiveness of caffeic acid mL caffeic acid, even though not significant, yet obvious inhibition of tumour nodule formation was observed, which was shown by a smaller visible mass (with average of 12.71 mm 3 ) (Figure 2B).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…(19,20) Studies have shown that caffeic acid triggers MG-63 osteosarcoma cell apoptosis by activating caspases (21,22) and may affect intrinsic and extrinsic apoptotic pathways. (23) Protein kinase C delta (PKCδ) has been reported to be involved in apoptosis of several cancer cells, including lung (24) and prostate cancer. (25) This protein is translocated from cytosol to various organelles, including mitochondria, in the presence of apoptotic stimuli, such as anticancer agents.…”
Section: Introductionmentioning
confidence: 99%